La literatura entre la historia y el mercado: Capítulo. La historia de la literatura argentina - José Luis de Diego (Cuadernos LIRICO)
Capítulo. La historia de la literatura argentina was a collection of fascicles and small books, published by the Centro Editor de América Latina in two versions: the first in 1967-1968 and the second, expanded, in 1979-1982. Here we seek to analyze the historiographic conception that supports the collection, its close relationship with the publishing market and the theoretical, critical and contextual differences between both stages. From this view, we're making an attempt to reconstruct the debate on history and literature in Argentina from the 1960s to the early 1980s.